Enzymatic and Bio-Inspired Enantioselective Oxidation of Non-Activated C(sp3)–H Bonds - Palone, Andrea; Bietti, Massimo; Costas, Miquel (Synthesis, 2024)
The enantioselective oxidation of C–H bonds relies on two different approaches: the use of enzymes or bio-inspired transition metal catalysts. Both are powerful tools, as they transform ubiquitous C(sp3)–H bonds into valuable oxygenated building blocks. However, the reaction remains a challenge in synthetic chemistry, continuously demanding efficient catalytic systems to improve substrate scopes. Optimization of site- and enantioselectivities in bio-catalytic systems is underpinned by protein engineering, while ligand design and medium effects play crucial roles in bio-inspired synthetic complexes. In this Short Review, recent advances in the field are described, focusing on reactions that target strong, non-activated C–H bonds.1 Introduction1.1 Enantioselective Catalytic C–H Oxidation in Nature and Bio-Inspired Systems1.2 Biological C–H Oxidation Mechanism and Challenges for the Implementation of Chirality with Synthetic Catalysts1.3 Bio-Catalytic C–H Oxidation Systems: From Microorganism to Engineered Enzymes1.4 Mimicking Nature: The Bio-Inspired C–H Oxidation Approach1.5 Origin of Enantioselectivity2 Enantioselective C–H Oxidation of Non-Activated C–H Bonds2.1 Hydroxylation at Non-Activated C–H Bonds by Bio-Catalytic Systems2.2 Enantioselective C–H Lactonization with Enzymatic Systems2.3 Oxidation at Non-Activated C–H Bonds by Synthetic Catalysts2.4 Enantioselective Lactonization with Small-Molecule Catalysts3 Conclusions
Keywords: cytochrome P450; enantioselectivity; oxidation; bio-inspired catalysts; C–H bond functionalization; hydrogen atom transfer; H2O2; oxygenases; aliphatic C–H hydroxylation